2010
DOI: 10.3122/jabfm.2010.05.100071
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Electrodiagnostic Testing Conducted in Primary Care

Abstract: Background: Focal and generalized neuropathies, such as carpal tunnel syndrome and diabetic peripheral neuropathy, have high prevalence among the US population. Primary care physicians are increasingly using computerized electrodiagnostic (EDX) testing to evaluate these patients. The impact of this diagnostic modality on physician diagnostic reasoning and patient management has not been directly studied.Methods: Consecutive computerized EDX tests conducted in a primary care clinic were prospectively evaluated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
1
3
0
Order By: Relevance
“…Before-and-after studies are promoted as a useful method for assessing the therapeutic impact of a diagnostic test (Guyatt et al, 1986). Our data and other studies have shown that electrodiagnostic test results have a notable impact on treatment plans for CTS (Boniface et al, 1994; Cho et al, 2004; Kothari et al, 1998; Shepherd, 2010). For surgeons that manage CTS on the basis of objective pathophysiology rather than symptoms, electrodiagnostic test results often lead to changes in recommended treatment.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Before-and-after studies are promoted as a useful method for assessing the therapeutic impact of a diagnostic test (Guyatt et al, 1986). Our data and other studies have shown that electrodiagnostic test results have a notable impact on treatment plans for CTS (Boniface et al, 1994; Cho et al, 2004; Kothari et al, 1998; Shepherd, 2010). For surgeons that manage CTS on the basis of objective pathophysiology rather than symptoms, electrodiagnostic test results often lead to changes in recommended treatment.…”
Section: Discussionsupporting
confidence: 71%
“…Prior studies had similar findings. In a prospective study of patients with focal and generalized neuropathies, including CTS, electrodiagnostic test results triggered a change in clinical management in 30% of patients (41% of patients with CTS) (Shepherd, 2010). Similarly, electrodiagnostic testing changed the treatment plan in 41% of patients with suspected polyneuropathy (Cho et al, 2004) and 46% of patients with suspected neuromuscular diseases (CTS, cervical radiculopathy, lumbosacral radiculopathy, etc.)…”
Section: Discussionmentioning
confidence: 99%
“…5,[6][7][8][9][10][11] The clinical diagnosis is most commonly confirmed by electrodiagnostic (EDX) studies as the reliable, differentiating, and the most objective diagnostic test. 5,6,9,12,13 Severity of carpal tunnel syndrome can also be evaluated by EDX, done bilaterally. 14 Repetitive strain and overuse of the wrist flexor tendons has been suggested as the cause of inflammation and eventually encroachment of the median nerve in wheelchair users.…”
Section: Introductionmentioning
confidence: 99%
“…In their study, the AUC calculated by the same method as the present study was 0.88 Therefore, NCA assessment using DPNCheck is thought to have excellent reliability and acceptable accuracy to identify diabetic polyneuropathy. The usefulness of NCA assessment using DPNCheck has been reported in peripheral neuropathy other than diabetic polyneuropathy, such as chemotherapy‐induced peripheral neuropathy and carpal tunnel syndrome. Thus, this POCD for nerve conduction study might be expected to be widely used in many fields of clinical practice.…”
Section: Discussionmentioning
confidence: 95%